Murder at the Serpentine Bridge - Penrose, Andrea (Penrose, Andrea. Wrexford & Sloane historical mystery., 2022)
"Charlotte, now the Countess of Wrexford, would like nothing more than a summer of peace and quiet with her new husband ... But when Wrexford and their two young wards, Raven and Hawk, discover a body floating in Hyde Park's famous lake, that newfound peace looks to be at risk. The late Jeremiah Willis was the engineering genius behind a new design for a top-secret weapon, and the prototype is missing from the Royal Armory's laboratory. Wrexford is tasked with retrieving it before it falls into the wrong hands"--